Regulatory and Legal Pressures and the Costs of Nasdaq Trading - Schultz, Paul (Review of Financial Studies, 2000)
The Nasdaq market came under intense pressure from regulators and class-action lawsuits following allegations of tacit collusion by Christie and Schultz (1994). This article examines the changes in transaction costs on the Nasdaq from January 1993 through June 1996 using 16 million trades in 30 stocks. Effective spreads cannot be estimated during 1995 and 1996 because time-stamps of trades and quotes cannot be matched. However, the autocovariance spread estimator of Roll (1984) works well with intraday data over this period. This spread estimator reveals that trading costs declined significantly for 29 of the 30 stocks over 1993-1996.